Breeding of the Scuttle Fly Megaselia scalaris in a fish Carcass and Implications for the use in Forensic Entomology (Diptera: Phoridae). - Moretti, Thiago de Carvalho [UNESP]; Thyssen, Patricia Jacqueline [UNESP]; Solis, Daniel Russ (E Schweizerbart'sche Verlags, 2009)
The breeding of 138 specimens of the scuttle fly Megaselia scalaris (Loew 1866) in a piece of sardine, Sardinella brasiliensis (Steindachner 1879) (Teleostei: Clupeidae), exposed in a rural site in SE Brazil is reported. Some aspects regarding the exploitation of carcasses of such nature and size by phorids are discussed, aiming to comprehend their potential forensic utility.
Keywords: Megaselia scalaris (Loew 1866); fish carrion; necrophagous flies; Neotropical region; forensic sciences